ANALYSIS OF FACTORS INFLUENCING THE DECISION TO USE MOBILE BANKING IN CUSTOMERS OF BANK BRI SEMARANG SUDIARTO BRANCH - Yan Abdillah; Susilo Toto Raharjo (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
ABSTRACTTechnology is advancing quickly, reshaping communication, payment systems, and the economy. Mobile banking, in particular, has the potential to revolutionize banking services by enabling customers to perform transactions independently. This research investigates the factors that influence the use of mobile banking among customers of PT Bank Rakyat Indonesia (Persero) Tbk at the Semarang Sudiarto Branch. The study targets active users of the BriMO Mobile Banking application, which serves 49,000 customers at this branch. A simple random sampling method was used to select 100 respondents, without considering population strata. Results show that mobile banking performance positively affects usage decisions, with a coefficient of 0.818 and a significance of 0.001 (H1 accepted). In contrast, mobile banking transaction costs negatively impact usage decisions, with a coefficient of -0.159 and significance of 0.014 (H4 accepted). Additionally, the decision to use mobile banking is positively associated with usage levels, indicated by a coefficient of 0.434 and significance of 0.001 (H5 accepted). However, ease of use (H2 rejected) and security trust (H3 rejected) do not significantly influence usage decisions, with significance values of 0.150 and 0.325, respectively.Keywords: Mobile Banking Performance, Ease of Use, Mobile Banking Security Trust, Mobile banking transaction costs, Decision to Use.